What is the relationship between FDI and economic growth? : Evidence from EU15 countries - Bilas, Vlatka (Array, 2020)
The aim of the paper is to examine the relationship between foreign direct investment (FDI) and economic growth in EU15 countries over the period 2002-2018. EU15 makes a group of countries which entered the EU prior to the biggest enlargement in 2004, namely latest in 1995 (Austria, Belgium, Denmark, Finland, France, Germany, Greece, Ireland, Italy, Luxembourg, Netherlands, Portugal, Spain, Sweden and United Kingdom). Paper findings contribute to the existing literature on the impact of FDI on economic growth. It employs different unit root tests, panel cointegration test (ARDL model) and Granger causality. Estimated panel ARDL model found some evidence that there are long-run equilibrium between LogGDP, LogFDI and LogFDIP series. The rate of adjustment back to equilibrium is between 4.43% and 5.95%. The long-run coefficients are all positive, but not all of them are statistically significant. In case of LogFDIP series long-run coefficients are statistically significant, varying between 0.1226 and 0.4398. These coefficients indicate that 1% increase in LogFDIP (logarithm of FDI to GDP) increases LogGDP between 0.1226% and 0.4398%. Results of Dumitrescu-Hurlin panel causality test indicated that there is only unidirectional causal relationship from GDP growth rate to FDI growth rate, and from GDP growth rate to LogFDIP. Conclusively, there is only a weak evidence that FDI had statistically significant impact on the GDP in EU15 countries.